Experience of living with knee osteoarthritis: a systematic review of qualitative studies - Nicholas F Taylor; Samantha Bunzli; Jason A Wallis; Nora Shields (BMJ Open)
Objectives Systematically review the qualitative literature on living with knee osteoarthritis from patient and carer perspectives.Design Systematic review of qualitative studies. Five electronic databases (CINAHL, Embase, MEDLINE, PsycINFO, SPORTDiscus) were searched from inception until October 2018. Data were synthesised using thematic and content analysis.Participants Studies exploring the experiences of people living with knee osteoarthritis, and their carers were included. Studies exploring experiences of patients having participated in specific interventions, including surgery, or their attitudes about the decision to proceed to knee replacement were excluded.Results Twenty-six articles reporting data from 21 studies about the patient (n=665) and carer (n=28) experience of living with knee osteoarthritis were included. Seven themes emerged: (i) Perceived causes of knee osteoarthritis are multifactorial and lead to structural damage to the knee and deterioration over time (n=13 studies), (ii) Pain and how to manage it predominates the lived experience (n=19 studies), (iii) Knee osteoarthritis impacts activity and participation (n=16 studies), (iv) Knee osteoarthritis has a social impact (n=10 studies), (v) Knee osteoarthritis has an emotional impact (n=13 studies), (vi) Interactions with health professionals can be positive or negative (n=11 studies), (vii) Knee osteoarthritis leads to life adjustments (n=14 studies). A single study reporting the perspectives of carers reported similar themes. Psychosocial impact of knee osteoarthritis emerged as a key factor in the lived experience of people with knee osteoarthritis.Conclusions This review highlights the value of considering patient attitudes and experiences including psychosocial factors when planning and implementing management options for people with knee osteoarthritis.Trial registrationnumberCRD42018108962